Stronghold : one man's quest to save the world's wild salmon - Malarkey, Tucker (Spiegel & Grau, 2019)
"Stronghold tells the story of Guido Rahr, a passionate and eccentric environmentalist who has single-mindedly dedicated his life to saving the environment, working to preserve the world's last pristine stronghold (habitat) for salmon in Russia's Far East--a landscape of ecological richness and diversity that is rapidly being developed for oil, gas, minerals, and timber in the Putin era. A high school drop-out and rebel more at home in the natural world among animals than among people, Rahr is a passionate fly fisher. His preternatural ability to understand the fish he was catching led him to fear for their future. What he came to understand is that the fate of the salmon is linked with the fate of humanity, as they contribute in essential ways to our own habitat. Deeply reported and beautifully written, Malarkey's book reveals the astonishing natural history of the salmon, while also providing a fascinating narrative that takes the reader to remote, inhospitable terrain and into the world of Russian oligarchs, corrupt officials, and impenetrable bureaucracies--as well as bringing us as close as possible to an extraordinary species of endangered fish. It is also a personal book in that Malarkey is Rahr's first cousin and spent her summers with him on their family's cabins in the wilds of Oregon. She has accompanied Rahr on many of his expeditions and knows this elusive, private, brilliant man as few do--